Survey of Indigenous Plants Used as Anthelminthic in Benue South Geopolitical Zone of Benue State, Nigeria - Apuu , V.K.; Igho-Osagie , U.P. (International Journal of Scientific Research in Biological Sciences, 2023)
the traditional knowledge of medicinal plants is fast disappearing as a consequence of modernization. This survey aimed at documenting indigenous plants used for the treatment of anthelmintic infections in the Benue South geopolitical zone of Benue State, Nigeria. Plant samples were collected from the field from twenty different locations including Otobi, Allan, Otukpo town central, Adoka-icho, Ochobo, Agadagba, Onyangede, Atilo, Ugbokolo, Ichama, Eke, Okpoga, Igumale, Utonkon, Agila, Ulayi Odiapa, Orihi, Obarike-Ito, and Obeko. The survey was carried out with the use of well-thought-out questionnaires in order to gather records on the plants usage as anthelminthic from traditional healers, herbalists, elders, and indigenous people. Collected plant samples were appropriately identified following standard protocols. Eighteen (18) plant species were collected, of which Carica papaya and Musa parasidiaca had the highest occurrence of (9%) while Albizia lebbeck, Urtica dioca, and Ficus exasperata had the least occurrence of (2.7%). Fabaceae and Rutaceae were the most represented plant families (11.1%). Among the different methods of preparation, Decoction (60%) had the highest occurrences whereas Squeezing (4%) had the least. On plant parts used, leaves (69.20 %) had the highest frequency of use while Fruits (7.7%) had the least. Based on findings from this study, Benue South geo-political zone has a great diversity of plants which are used for the management of Helminthic Infections. The study recommended that further research be carried out on the identified plant species to determine their efficacy and active biochemical compounds.